Nursing competency and organizational climate as perceived by staff nurses in a Chinese university hospital - Liu Ying (2018)
Nursing competency is important to ensure patient safety and improve the quality of nursing care. Based on competency-based human resource management strategies, the organizational climate can positively influence nursing competency. However, a review of the literature indicated that there were no studies about the relationship between nursing competency and organizational climate in the People's Republic of China. This descriptive, correlational study examined the relationship between nursing competency and the organizational climate. The sample consisted of 243 staff nurses who completed the questionnaire worked at one university hospital in Liao Ning Province. The findings showed that there was a significantly moderate positive relationship between nursing competency and organizational climate. The study results suggested that Chinese nurse managers should maintain and provide a positive organizational climate to improve nursing competency. © 2007 The Authors; Journal Compilation © 2007 Blackwell Publishing Asia Pty Ltd.